How to assess the effectiveness of energy management processes in water supply systems - Carriço, N. (2013)
Asset management is assuming higher relevance in utilities’ short and long term management. Governance and policies are playing an important role in the process and, in some countries, regulators and governments are assuring that asset management methodologies are properly followed. Utilities and their stakeholders should deal with different ‘renewal policies’ approaches, towards better planning processes and a more sustainable way of managing capital expenditure in the long term. AGS is a Portuguese private operator with contractual responsibilities in 17 concessions and PPPs. Asset management is an important matter for the entire organisation, as a management process and, since 2009, as a legal obligation. The present paper will describe infrastructure asset management policies in the organisation and the initiative’s roadmap in order to present major concerns, tools and methods, its usage, and the results perceived.